Peripartum Cardiomyopathy - Das, UK; Ahsan, SA; Nahar, L (University Heart Journal, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Peripartum Cardiomyopathy (PPCM) is an uncommon form of congestive heart failure that affects women in late pregnancy or early puerperium. The disease causes a significant morbidity and mortality in women of child bearing age. The etiology is unknown and diagnosis is confined to a narrow period and requires echocardiographic evidence of left ventricular systolic dysfunction. Dyspnoea is the main presenting complaint but carries a broad differential diagnosis. Although PPCM is an uncommon disease it should be considered in the differential diagnosis in women presenting with dyspnoea in the late pregnancy or early puerperium. Treatment of PPCM is similar to that of other forms of congestive heart failure and included loop diuretics, beta blockers, vasodilators and digoxin. With early and effective treatment a significant number of patients improve but in others it carries a long term poor prognosis. We are presenting a case of PPCM in a 30-years old woman who presented with dyspnoea after fifteen days of parturition. Â Â Â Â Â University Heart Journal Vol.4(1) January 2008